Self-Management Skills as a Basis for the Effectiveness of e-Learning - M. A. Lukashenko (Высшее образование в России)
The pandemic has forced universities to switch to e-Learning in force majeure mode. This served as a powerful impetus for the accelerated arming of universities with the resources that allow effective online and blended learning. In these conditions, it became possible to implement a learner-centered educational paradigm. However, this is hindered by the problem of the student’s lack of self-organization and self-motivation skills, as well as the lack of their ability to take responsibility for their own learning and development. This problem is gaining more and more theoretical and practical importance. The purpose of the work is to substantiate that courses such as self-management and time management contribute to the formation of competencies in the field of goal-setting, planning, self-organization, self-control and self-motivation, and therefore in the context of the implementation of learner-centered paradigm, they should serve as propaedeutics for е-Learning. For this purpose, the article provides a review of the content of the “Time Management” course in relation to the task of developing proactivity and the student’s ability to systematic and productive independent work.